PENGARUH PERSEPSI SISWA TENTANG CARA MENGAJAR GURU, EFIKASI DIRI, TEMAN SEBAYA, FASILITAS BELAJAR, LINGKUNGAN KELUARGA TERHADAP MINAT BELAJAR SISWA KELAS XI PADA MATA PELAJARAN EKONOMI DI SMA N 6 SOLOK SELATAN - Zikri, Afdal; Amelia, Mona; Eprillison, Vivina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze: 1) the influence of students' perceptions of teachers' teaching methods on learning interest, 2) the influence of self-efficacy on learning interest, 3) the influence of peers on learning interest, 4) the influence of learning facilities on learning interest, 5) the influence of the family environment on learning interest. The type of research used in this study is associative research. The research was conducted in August 2025. The population in this study is all tenth-grade students in economics at SMAN 6 Solok Selatan. The sample in this study consists of 110 people. The sampling technique used is Random Sampling, and the data analysis techniques used are descriptive analysis and inductive analysis, assisted by Eviews and SPSS version 21.0. The research results show that 1) there is an influence of students' perceptions of teachers' teaching methods on learning interest with a coefficient value of 0.670 and a t-value calculated > t-table 8.388 < 1.65964 and a significance value of 0.000 < 0.05, 2) there is an influence of self-efficacy on learning interest with a coefficient value of 0.221 and a t-value calculated > t-table 3.349 < 1.65964 and a significance value of 0.001 < 0.05, 3) there is an influence of peer relationships on learning interest with a coefficient value of 0.184 and a t-value calculated > t-table 0.954 > 1.65964 and a significance value of 0.342 > 0.05, 4) There is an influence of learning facilities on learning interest with a coefficient value of 0.663 with a t-count value > t-table 3.367 < 1.65964 and a significant value of 0.001 < 0.05, 5) there is an influence of the family environment on learning interest with a coefficient value of -0.144 with a t-count value > t-table -1.984 < 1.65964 and a significant value of 0.050 < 0.05. 6) 1. Students' perceptions of teachers' teaching methods, self-efficacy, peer influence, learning facilities, and family environment collectively (simultaneously) have a significant effect on learning interest. It was found that the calculated F value is 25.311 > 2.30 from the F table and the significant value is 0.000 < 0.05.